AN ASSESSMENT OF THE GROWTH AND TRENDS IN UZBEKISTAN’S DOMESTIC TOURISM - Mamasodiqova Khojirakhon Ulug’bek qizi (PEDAGOGS, 2025)
Abstract: Uzbekistan possesses significant potential for both international and domestic tourism, driven by its rich material and cultural heritage, diverse natural landscapes, unique national cuisine, and renowned hospitality. This article aims to analyze the development of internal tourism within the republic, capitalizing on these inherent opportunities.